The Challenge of Terrorism Regeneration: What Schools Do Terrorist Offenders Select for Their Children? - Sukabdi, Zora Arfina; Sofanudin, Aji; Munajat, Munajat; Mulyana, Mulyana; Budiyanto, Sigit (Universitas Islam Negeri Mataram, 2025)
Children's education plays a crucial role in preventing radicalization. By fostering analytical thinking and encouraging an evidence-based approach, education can help children develop the ability to discern and challenge extremist narratives. This study aims to investigate the terrorist offenders’ children's education in Indonesia through qualitative and quantitative research designs. By interviewing terrorist prisoners, holding discussions with former prisoners, and reviewing legal documents of terrorism cases such as profiling and assessment reports, this study tries to identify the regeneration of terrorist networks in Indonesia. The study examines the schools terrorist offenders (as decision makers) select for their children. The findings of this study show that only 18% of prisoners’ children are sent to schools not associated at all with terrorist organizations. In comparison, prisoners hide 29%, 14% are sent to schools less affiliated with terrorist organizations, and 13% are in schools very affiliated with terrorist organizations. This indicates distressing information that the indoctrination of youngsters persists within terrorist networks in Indonesia. Moreover, there are correlations between several independent (e.g., offenders' sentences, risk levels, and affiliations) and dependent variables (e.g., children's trauma, categories of school, orientations, and school networking). The study may help predict the continuation and recurrence of terrorism.